2019
DOI: 10.1101/665190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal TORC1 modulates longevity via AMPK and cell nonautonomous regulation of mitochondrial dynamics inC. elegans

Abstract: 14Target of rapamycin complex 1 (TORC1) and AMP-activated protein kinase (AMPK) 15 antagonistically modulate metabolism and aging. However, how they coordinate to 16 determine longevity and if they act via separable mechanisms is unclear. Here, we show 17 that neuronal AMPK is essential for lifespan extension from TORC1 inhibition, and that 18

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…It is well‐established that changes in mitochondrial function can signal throughout organisms to extend C. elegans lifespan 70 . In addition, neuronal AMPK mediates longevity in C. elegans and is interconnected with other metabolic pathways that affect mitochondrial morphology 72 . Our results complement each of these findings and suggest that the PMF may be the source change that leads to signaling downstream to affect physiology.…”
Section: Discussionsupporting
confidence: 74%
“…It is well‐established that changes in mitochondrial function can signal throughout organisms to extend C. elegans lifespan 70 . In addition, neuronal AMPK mediates longevity in C. elegans and is interconnected with other metabolic pathways that affect mitochondrial morphology 72 . Our results complement each of these findings and suggest that the PMF may be the source change that leads to signaling downstream to affect physiology.…”
Section: Discussionsupporting
confidence: 74%
“…Also, Zhang et al . showed that the lifespan extension of s6k null mutant in C. elegans is suppressed by neuronal expression of s6k (Y. Zhang et al., 2019). While the nervous system of C. elegans is not organized into a brain with higher‐order structures and domains, our findings show that lifespan regulation by a small number of brain neurons may be an evolutionarily conserved phenomenon in the Drosophila brain, which shares functional analogous organization with higher organisms.…”
Section: Discussionmentioning
confidence: 99%
“…AAK-2 (AMPK) is another crucial metabolic energy sensor that links nutrient availability to lifespan ( 18 ). AMPK regulates mTORC1 activity and shares downstream effectors of lifespan modulation with mTOR ( 87 ). AMPK can also regulate mammalian FOXO3 ( 88 ).…”
Section: Dietary Restriction Extends Lifespan In C Elegansmentioning
confidence: 99%